(untitled) (Research, Society and Development, 2020)
The process of initial and continuing document formation is extremely important for the success of your professional career. However, it is commonly reported the presence of professionals teaching different disciplines in their area of training and there are also professionals without continuing education. Factors like these can directly interfere with the quality of students’ teaching and learning. Thus, the presente study aimed to outline the socio-professional profile and investigate the initial and continuing education of teachers in the Science discipline who teach in the state network of the municipality of Mossoró-RN. For this, a cross-sectional, descriptive, retrospective study with a quantitative approach was carried out, with the target population being teachers of the Science discipline of 20 schools in the state network of Mossoró-RN. It can be seen that the predominant age group of teachers is between 36-45 years (57.2%), the majority are women (57%), the most frequent civil status is married (42%), 56% of professionals have childrens. In relation to the work regime, 57% have a workload of 60 hours per week, complement the workload with another discipline and have between 5-10 years of teaching career. When the initial training is evaluated, it can be seen that all professionals have completed higher education at the State University of Rio Grande do Norte and that 57% have a degree in Biological Sciences. Finally, when evaluating continuing education, it is observed that 71% took graduate courses in the specialization modality, but do not carry out continuous training activities. Thus, it is observed that most professionals who teach the discipline of Sciences in the state network of the city of Mossoró-RN, have initial and continuing training, but they miss training courses for recycling knowledge. Thus, the work proposes the creation of participatory intervention projects that integrate public school teachers to update their knowledge.